Calculation and Analysis of Deformation Characteristic and Energy Dissipation of Flexible Bearings in Harmonic Drive for Industrial Robots. Issue 1 (1st November 2022) - Xu, Zhaoxiang; Wang, Yazhen; Wang, Haifeng
Abstract: The flexible bearing is a key component of harmonic gear reducer for industrial robots. The wave generator cam as assembly part will significantly affect the flexible bearing transmission state. This paper derives the flexible bearing deformation coordination equation formula based on the harmonic drive theories, and the deformation characteristics of the flexible bearing formed by different wave generator cam shapes were studied. Combined the theory of clabellon with the load and deformation which are obtained, the deformation energy dissipation of the outer ring of the flexible bearing is discussed and quantitatively evaluated. The results showed that the wave generator cam shapes have a greater effect on the carrying capacity of the flexible bearing, and the dissipation of deformation energy of the flexible bearing can be effectively reduced by selecting appropriate wall thickness of the outer ring. Moreover, it was found that the two-roller wave generator deformation energy dissipation is the least at the same constraint.